Determination of the Effects of Z. officinale and Propolis Extracts on Intestinal Microbiology and Histological Characteristics in Broilers - Tekeli, A.; Kutlu, H.R.; Celik, L.; Doran, F. (International Journal of Poultry Science, 2010)
The purpose of this study is to explore the effects of Z.officinale and propolis extracts on intestine microbiology and histology in broilers as alternative growth promoters to antibiotics. One-day-old, Ross 308 male broiler chicks were used in the experiment. At the beginning of the experiment, seven treatment groups [negative control, positive control, Z. officinale, propolis and three different combinations of Z. officinale + propolis (0.5 + 0.5, 1 + 1 and 1.5 + 1.5)] were formed with similar mean weight, comprising 16 birds each. Each group was fed ad libitum for 42 days. Supplementation of Z. officinale and propolis extracts alone or in combination reduce Coliform bacteria (p<0.05) compared to negative control group. The highest numbers of total mesophilic aerobic bacteria was identified in the group with (1:1) combination of Z. officinale + Propolis (p<0.05). The high amount of such bacteria in this group can be attributed to the lack of Coliform bacteria and decreasing tendency in E. coli content. The desired stimulating effect on lactic acid bacteria was observed in all treatment groups compared to negative control group. Z. officinale and Propolis extracts and their combinations significantly improved intestinal villi length (p<0.05) compared to negative control group. These affirmative findings indicate likely improvement in performance parameters of animals in treatment groups. As a result; Z. officinale and Propolis extracts could have a great potential to promote broiler growth.